ssODN-Mediated In-Frame Deletion with CRISPR/Cas9 Restores FVIII Function in Hemophilia A-Patient-Derived iPSCs and ECs - Zhiqing Hu; Miaojin Zhou; Yong Wu; Zhuo Li; Xionghao Liu; Lingqian Wu; Desheng Liang (Molecular Therapy: Nucleic Acids, 2019)
Given that the cDNA of F8 is too large to be packaged into adeno-associated virus (AAV) capsids, gene transfer of some versions of B-domain-deleted F8 (BDD-F8) for hemophilia A (HA) treatment has been attempted with promising results. Here, we describe an efficient gene correction via single-stranded-oligodeoxynucleotide (ssODN)-mediated in-frame deletion within the B domain of F8 with CRISPR/Cas9 in HA-patient-derived induced pluripotent stem cells (HA-iPSCs). The expression and activity of FVIII was restored in corrected HA-iPSC-derived induced endothelial progenitor cells (C-iEPCs) in vitro and in vivo. The bleeding phenotype was rescued in HA mice after C-iEPC infusion. Our results demonstrate an efficient approach for in situ gene correction via introduction of a tiny deletion using ssODN and CRISPR/Cas9 to reframe the F8 transcript and restore FVIII function in HA-iPSC-derived EPCs with potential clinical impact in HA gene therapy. For the first time, we demonstrated in vitro and in vivo the FVIII function that is encoded by the endogenous F8 gene with a partially deleted B domain. This work also suggests an applicable strategy for genetic correction of other gene frameshift mutations. Keywords: hemophilia A, CRISPR/Cas9, ssODN, iPSCs, in-frame deletion, gene therapy